IT outsourcing - A source of innovation? Microeconometric evidence for Germany - Bertschek. Irene; Daniel Erdsiek (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Do firms sourcing out IT services redirect their resources to innovation activity? We attempt to answer this question by analysing a firm-level data set comprising 1453 firms from the German manufacturing and services sectors. Using different measures of IT outsourcing (ITO), the econometric estimations reveal a significant and U-shaped relationship between ITO and product innovation activity of manufacturing firms, and a significant and hump-shaped relationship between ITO and process innovation activity of services firms. A propensity score matching analysis takes account of reverse causality; the results underpin the relevance of ITO for services firms' realisation of process innovation.
Keywords: D22; L23; O31; 330; IT outsourcing; product innovation; process innovation; firm-level data